Co-pay and Feel Okay: Evidence of Illusory Health Gains from a Health Insurance Reform - Alfredo R. Paloyo (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
The reliability of general self-rated health status is examined using the reform of the public health insurance system of Germany in 2004 as a source of exogenous variation. Among others, the reform introduced a co-payment for ambulatory doctor visits and increased the co-payments for prescription drugs. This natural experiment allows identification of the causal impact of the program on self-assessed health and hence reveals the sensitivity of this subjective measure to a perturbation in the insurance system. Using data from the German Socio-Economic Panel, the results indicate that after the policy intervention, the respondents in the treated group perceived their own health status as better than their hypothetical untreated state even when there is no discernible impact on actual health.
Keywords: G22; H43; I18; 330; Natural experiment; cognitive dissonance; self-rated health status; Gesundheit; Meinung; Gesundheitsreform; Selbstbeteiligung (Versicherung); Wirkungsanalyse; Deutschland